Thiolated layered double hydroxide-based nanoparticles: A study on mucoadhesiveness and cytotoxicity - Senturk, Sema; Kaplan, Ozlem; Bal, Kevser; Topcu, Kubra Sen Bas; Gok, Mehmet Koray; Topcu, Kübra Sena Baş (Elsevier, 2025)
The aim of this study was the synthesis and characterization of thiolated Mg/Al Layered double hydroxide nanoparticles (nLDH) that can adhere to mucosal surfaces. For this purpose, initially, nLDH were synthesized and then their surface was modified with L-cysteine (Cys). Then the Cys-modified nanoparticle structure (nLDHCys) Cys ) was characterized by FTIR, XRD and FE-SEM/EDS, and the amount of thiol groups was determined using the iodometric method. The cytotoxicity properties of nLDH and LDHCys Cys were examined on cervical (HeLa), fibroblast (L929) and colon (HT29) cell lines. In addition, the adhesion of nanoparticles to mucosal surfaces has been evaluated through mucin interaction experiments and ex vivo tests on ewe vaginal tissue. The results from characterization studies prove that Cys molecule has been successfully modified on the surface of nLDH. Cytotoxicity studies demonstrated that Cys modification did not negatively affect the cell viability, and these results were extremely close to those of nLDH. Ex vivo tests on ewe vaginal tissue and mucin interaction demonstrated that nLDHCys Cys enhanced retention on the mucosal surface. Considering their retention ability to mucosal surface and their biocompatible nature, nLDHCys Cys is expected to play an important role as a promising option for a safe mucoadhesive nanoparticle system for biological applications in the future.
Keywords: Mucoadhesion; Thiolation; Thiolated Ldh Nanoparticles; Surface Modification Of Ldh